Genetic and environmental overlap between delinquent peer association and delinquency in adolescence - Boisvert, Danielle (Criminal justice and behavior, 2014)
Delinquent peer association and criminal/delinquent behaviors are highly intertwined. The directionality and mechanisms underlying this relationship, however, have been debated in the literature for decades. The current study seeks to further inform this debate by examining whether individual differences at the level of the genome can help to explain the association between delinquent peer affiliation and delinquency. Using the twin and full-sibling subsample from the National Longitudinal Study of Adolescent Health (Add Health), behavioral genetic methodology is used to examine whether delinquent peer affiliation and delinquency in adolescence covary as the result of common genetic factors. Results indicate that delinquent peer association and delinquency are moderately influenced by additive genetic factors, and that common genes are in fact influencing the covariance between the two outcomes. The importance of incorporating genetic explanations into traditional theories of delinquency is discussed.